Potential benefits of climate change on navigation in the northern sea route by 2050 - Mohamed Rami Mahmoud; Mahmoud Roushdi; Mostafa Aboelkhear (Scientific Reports, 2024)
Abstract Climate change has been inducing a continuous increase in temperatures within the Arctic region, consequently leading to an escalation in the rates of Arctic ice depletion. These changes have profound implications for navigation along the Arctic Northern Sea Route (NSR). However, access to the NSR is constrained to specific temporal intervals when the sea ice thickness reaches a threshold that permits safe passage of ships. This research employs climate change model simulations and the Polar Operational Limit Assessment Risk Indexing System framework to investigate the navigational feasibility of diverse ship types along NSR during the calendar years 2030, 2040, and 2050, under SSP2-4.5 and SSP5-8.5 scenarios. Different ship categories were analyzed within the context of these two scenarios. Results indicate considerable variation in the navigability of different ship categories across different scenarios and years. In general, polar ships demonstrate a higher navigational potential throughout most of the year, while pleasure crafts are constrained to specific periods. These findings bear significant implications for the future of shipping along the NSR. As Arctic ice continues to melt, NSR is anticipated to become more accessible to ships, albeit with navigational availability remaining contingent on the ship category and seasonal considerations.